(untitled) (Eurasian Journal of Ecology, 2016)
Humanity is totally depends on the Earth ecosystems and the services they provide. Degradation of ecosystems often causes significant damage to the welfare of humanity. Payments for ecosystem services are the modern economic tool restoration of ecosystems. The article deals to the possibilities of implementation of payments for ecosystem services in the Republic of Kazakhstan.